Գրիգոր Բ. Վկայասերի ձեռագրական ժառանգությունը - Հարությունյան, Քնար (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Католикосы Армении сыграли большую роль в создании и развитии армянских рукописных и печатных книг, будучи меценатами, получателеми, а многие и писцами. Поэтому для всесторонней оценки их роли, а также для изучения истории армянской книги важно представить эту сферу их деятельности. В этом отношении примечательна деятельность католикоса Григора II Вкаясера (1066–1105), сыгравшего большую роль в переводе агиографической литературы. Хотя до нас не дошли его рукописи, но изучение источников выявило прямые и косвенные свидетельства его участия в создании рукописей. Так, согласно литературным данным, Григор II Вкаясер попросил и получил от своего отца Григора Магистра труд «Толкования грамматики», а значит и рукопись. Также он привез с собой рукописи из Константинополя. По свидетельству поэта XII века Вардана Айказна, он собирал рукописи и выкупал их у врагов. Изучение колофонов и рукописных источников также дает информацию о конкретных рукописях Вкаясера. Так, в одной рукописи, написанной в 1298–1299 гг., есть сведения о том, что ее часть скопирована с рукописи католикоса и в ней цитируется колофон, написанный самим Вкаясером в 1078 г. Другое свидетельство дает рукопись, хранящаяся в Париже, которая тоже содержит колофон католикоса. Еще о двух рукописях можно предположить на основании его сочинений («Толкование на деяния святых апостолов», «История Иоанна Златоуста»), дошедших до нас лишь в копиях. The Catholicoses of Armenia played a great role in the creation and development of Armenian manuscripts and printed books, being patrons, recipients and many of them even scribes. Therefore, for a comprehensive assessment of their work, as well as for the study of the history of the Armenian book, it is important to present this area of their activity. In this regard, the activity of Catholicos Grigor II Vkayaser (the Martyrophile, 1066- 1105) is noteworthy as he played a great role in translation of hagiographic literature. Although his manuscripts did not survive, the study of the sources revealed direct and indirect evidences that he had been involved in the process of making a manuscript. So, according to literary data, Grigor II Vkayaser asked and received from his father Grigor Magistros the work “Meknutyun qerakani” (Interpretation of grammar) and hence the manuscript. He also brought with him manuscripts from Constantinople. According to the XII century poet Vardan Haykazn, he collected manuscripts and bought them from enemies. The study of colophons and handwritten sources also provides information about the specific manuscripts of Vkayaser. So, in one manuscript written in 1298- 1299, there is information that its part was copied from the Catholicos’s manuscript and it quotes a colophon written by Vkayaser himself in 1078. Another piece of evidence gives a manuscript kept in Paris, which also contains Grigor II Vkayaser’s colophon. About his two more manuscripts, we can assume on the basis of his writings (“Interpretation on the Acts of the Holy Apostles”, “History of John Chrysostom”), which have come down to us only in copies.
Keywords: Բանասիրություն